Awareness of age-related change, future time perspective, and implications for goal adjustment in older adulthood. (19th May 2022) - Wilton-Harding, Bethany; Windsor, Tim D.
Abstract: Objectives: How people adjust their goals is central to adaptation across the lifespan. However, little is known about individual difference characteristics that predict how and why people use different self-regulatory strategies. The present study investigated associations of perceived age-related gains and losses, and their interaction, as predictors of goal adjustment in older adulthood. Furthermore, we examined whether future time perspective (FTP) mediated relationships between awareness of age-related change (AARC) and goal adjustment. Method: A community-based sample of 408 adults (aged 60–88 years) was recruited via an internet-based research platform. Participants completed questionnaire measures of AARC, FTP, goal disengagement, and goal re-engagement. A flexibility index reflecting tendencies toward use of both goal disengagement and goal re-engagement strategies was also analyzed. Results: Although AARC-losses was associated with lower goal re-engagement and goal flexibility, this association was weaker among those with higher AARC-gains, indicating AARC-gains may be protective in the relationship between AARC-losses and goal adjustment. The association between AARC and goal adjustment was also shown to be mediated by FTP. Higher AARC-gains was associated with more expansive FTP, which was associated with lower goal disengagement and higher goal re-engagement. On the other hand, higher AARC-losses was associated with more restricted FTP, which was associated with higher goal disengagement and lower goal re-engagement. Discussion: Results have implications for how we conceptualize the combined effects of age-related gains and losses on developmental outcomes relevant to adaptive aging. Furthermore, perceptions of future time with advancing age may be implicated in processes linking AARC with goal adjustment.